Terapi NON FARMAKOLOGI BERBAHAN HERBAL UNTUK MENURUNKAN NYERI REMATIK : A LITERATURE RIVIEW - Rin Rin Karomattul Umaht; Hilman Mulyana; Rita Purwanti (Jurnal Keperawatan BSI, 2021)
With increasing age, the physiological function of the elderly will decrease and degenerative problems will reduce the body's resistance so that it is susceptible to infections and diseases, including rheumatism or joints. Several treatments to reduce pain, especially rheumatism with pharmacological and non-pharmacological measures such as complementary therapy. This research is to reduce pain using complementary therapy with herbal ingredients, such as ginger, lemongrass, cinnamon, Moringa leaves, lavender aromatherapy. The purpose of this study was to determine the best non-pharmacological therapy made from herbs to reduce rheumatic pain. This research method uses a literature review study using secondary data taken from national and international articles from 2011-2021 with the same theme. The results showed that from the 14 articles all were able to reduce rheumatic pain, but according to the results of the researcher's analysis there was one article that was considered the most effective for reducing rheumatic pain, namely using red ginger. It is hoped that both researchers and clients can find out in detail about the effective use of non-pharmacological therapy from the beginning to the end.